A Case of Infected Left Atrial Myxoma Presenting as ST-Elevation Myocardial Infarction (STEMI) - Peters, Matthew J. (Am J Case Rep, 2019)
Patient: Male, 34-year-old Final Diagnosis: Infected atrial myxoma Symptoms: Chest pain Medication: — Clinical Procedure: — Specialty: Cardiology OBJECTIVE: Rare disease BACKGROUND: Although left atrial myxoma is the most common benign primary cardiac tumor, infected atrial myxoma is rare. This report presents a case of infected left atrial myxoma with embolization to the left anterior descending (LAD) coronary artery, which was identified following an initial presentation with ST-elevation myocardial infarction (STEMI). CASE REPORT: A 34-year-old man with a history of smoking tobacco and intravenous cocaine use presented to the emergency room with symptoms of a feeling of pressure on the chest and symptoms in the left arm. An electrocardiogram (ECG) showed ST elevation in leads II, III, aVF, and V3–V5, consistent with an anterior-inferior STEMI. He underwent percutaneous intervention (PCI) with two drug-eluting stents to the mid-distal LAD coronary artery. The patient also had fever, chills, a history of weight loss, and signs of peripheral emboli. Blood cultures identified Gram-positive Streptococcus parasanguinis, a member of the Streptococcus viridans group. Transesophageal echocardiogram (TEE) identified a large, mobile, pedunculated left atrial mass protruding into the mitral valve in diastole and mitral valve vegetations. Surgical excision and the histology confirmed a diagnosis of benign left atrial myxoma containing Gram-positive cocci. The patient required mitral valve replacement and a postoperative two-week course of gentamicin and a six-week course of ceftriaxone CONCLUSIONS: A rare case is reported of infected left atrial myxoma presenting as STEMI secondary to coronary artery embolization, which was treated with PCI, antibiotics, and mitral valve replacement.